Transjugular intrahepatic portosystemic shunt for Budd–Chiari syndrome with diffuse occlusion of hepatic veins - He, Fuliang (Sci Rep, 2016)
Either acute or sub-acute Budd–Chiari syndrome (BCS) with diffuse occlusion of hepatic veins has a high mortality rate and remains challenging for clinical treatment. We aimed to evaluate the feasibility and safety of transjugular intrahepatic portosystemic shunt (TIPS) as a treatment for BCS with diffuse occlusion of hepatic veins. From January 2007 to December 2010, 100 patients were randomly recruited onto this study and 91 patients were treated with TIPS. 14 patients were defined as acute BCS group and 86 patients as sub-acute group. Patients with acute BCS had a significantly higher rate of jaundice whereas a lower rate of abdominal and chest varices, gastroesophageal variceal bleeding and refractory ascites than sub-acute group (P < 0.001). TIPS was technically successful in all 91 patients (12 in acute group). The portosystemic pressure gradient (PSG) was decreased to normal level, while total bilirubin (TBIL) and liver function were significantly improved. During follow-up period, the mortality rate of 91 patients who underwent TIPS was 6.59% (6/91), whereas 88.89% of 9 patients who didn’t receive TIPS procedure (2 in acute group). Collectively, TIPS is an effective and safe approach in treating BCS with diffuse occlusion of hepatic veins, which should be performed in time.